IMPLEMENTATION OF THE 1973 CONVENTION ON INTERNATIONAL TRADE IN ENDANGERED SPECIES OF WILD FAUNA AND FLORA (CITES) FOR THE PROTECTION OF ENDANGERED PANGOLIN SPECIES IN INDONESIA - Habiel, Muhammad; Fikri, Fikri (Universitas Syiah Kuala, 2024)
Indonesia is one of the most biodiverse countries in the world and is home to the rare pangolin (Manis javanica). Pangolins are protected under Appendix I of CITES and Law No. 5 of 1990 on the Conservation of Natural Resources and Ecosystems, following Indonesia's ratification of the CITES convention in 1978. However, illegal pangolin trade persists despite these protections. The purpose of this thesis is to analyze how CITES, in collaboration with Indonesia, contributes to preventing and controlling illegal pangolin trade, as well as safeguarding pangolin species under Law No. 5 of 1990. This research employs normative legal methods, including library research to gather and classify information from various sources. It also uses a case approach for an in-depth examination of related legal issues and a statutory approach to analyze the current legislation. The findings indicate that despite Indonesia's 46-year participation in the international CITES convention and the establishment of Law No. 5 of 1990, illegal pangolin trade continues. The criminal provisions of Article 40 of Law No. 5 of 1990 have proven ineffective in deterring environmental crime.